2022
DOI: 10.1186/s13100-022-00279-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the regulatory relationship between KRAB-Zfp clusters and their target transposable elements via a gene editing strategy at the cluster specific linker-associated sequences by CRISPR-Cas9

Abstract: Background Krüppel Associated Box-containing Zinc Finger Proteins (KRAB-ZFPs), representing the largest superfamily of transcription factors in mammals, are predicted to primarily target and repress transposable elements (TEs). It is challenging to dissect the distinct functions of these transcription regulators due to their sequence similarity and diversity, and also the complicated repetitiveness of their targeting TE sequences. Results Mouse KRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
0
0
Order By: Relevance
“…The majority of TE silencers were downregulated in pre-HECs compared to VECs and HSCs (for example, 84.07 and 77.49% of KRAB-ZFPs in human and mouse, respectively) (Fig. 4 C, F; Additional file 8 : Table S5 and S6; KRAB-ZFP genes are available from [ 66 ]). Among the downregulated KRAB-ZFPs, ZNF84, ZNF382, and ZNF429 were found to bind significantly to L1 superfamily in human [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of TE silencers were downregulated in pre-HECs compared to VECs and HSCs (for example, 84.07 and 77.49% of KRAB-ZFPs in human and mouse, respectively) (Fig. 4 C, F; Additional file 8 : Table S5 and S6; KRAB-ZFP genes are available from [ 66 ]). Among the downregulated KRAB-ZFPs, ZNF84, ZNF382, and ZNF429 were found to bind significantly to L1 superfamily in human [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Genes related to TE silencing were collected from the literature [ 41 , 43 ]. Potential KRAB-ZFP genes in human and mouse were obtained from [ 66 ]. The whole list of TE silencers analyzed in this study can be found in Additional file 8 : Table S5 and S6.…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, the majority of TE silencers were downregulated in pre-HECs against VECs and HSCs (for example, 84.07% and 77.49% of KRAB-ZFPs in human and mouse, respectively) (Fig. 4C, F; Additional file 7: Table S9 and S10; KRAB-ZFP genes are available from [63]). Among the downregulated KRAB-ZPFs, ZNF84, ZNF382 and ZNF429 were found to bind significantly to L1 superfamily in human [64].…”
Section: Te Silencers Are Transiently Relaxed In Pre-hecsmentioning
confidence: 99%
“…Genes related to TE silencing were collected from the literature [42,44]. Potential KRAB-ZFP genes in human and mouse were obtained from [63]. The whole list of TE silencers analyzed in this study can be found in Additional file 7: Table S9 and S10.…”
Section: Te Silencing and Sensing Analysismentioning
confidence: 99%